Synergistic benefits of olive pomace and multi-enzyme supplementation on fattening rabbit health and performance - Bakeer, Manal R.; El-Haroun, Ehab; Abdelnour, Sameh A. (Frontiers in Veterinary Science, 2025)
IntroductionDisposing of agricultural and forestry waste through incineration, as is common in current waste management practices, exacerbates environmental pollution. The olive oil industry produces substantial byproducts, including olive pomace (OP). Finding more cost-effective and environmentally friendly uses for these byproducts can help reduce waste, enhance resource efficiency, and promote a circular economy. This study evaluated the physiological response of rabbits, including metabolic parameters, digestive enzyme activities, and caecal fermentation characteristics, to diets partially substituted with yellow corn, OP, and/or a multi-enzyme complex (Kemzyme, KE).MethodsA total of 120 New Zealand white rabbits were divided into four groups (30 rabbits each). The control group (CON) received a basal diet, the olive pomace group (OP) had 10% olive pomace added to their feed, while the enzyme group (KE) received 0.5% Kemzyme and the combination group (OP+KE) obtained both supplements.ResultsBody weight increased significantly more in the OP+KE and KE groups compared to the other groups (p < 0.05). However, all supplemented groups had higher blood glucose and digestive enzyme (lipase and protease) activities compared to the control group (p < 0.05). Notably, total protein and DNA concentrations in duodenal tissue were augmented in the KE and OP+KE groups compared to the others (p < 0.05), suggesting enhanced cellular proliferation. Supplementing rabbit diets with enzymes, either alone or combined with OP, significantly increased total volatile fatty acid concentrations in the cecum compared to the control group (p < 0.05). All supplemented groups showed a significant improvement in butyric (p < 0.001) and propionic (p < 0.01) acid levels, coupled with a notable reduction in ammonia (p < 0.05). Furthermore, enzyme inclusion in the diet enhanced villus height and Brunner's gland size (p < 0.05) compared to the other groups.DiscussionThese findings indicate that supplementing rabbit diets with Kemzyme, either alone or alongside olive pomace, effectively improves metabolic parameters, digestive enzyme activities, and intestinal morphology. This represents a sustainable advancement in rabbit nutrition, integrating agricultural byproducts with enzyme technology.